Driving Lidl´s growth strategy in Portugal through customer loyalty: conceptualization of a loyalty program with high perceived value for its customers - Garcia, Joaquim João De Meira (2021)
This Work Project aims to find a solution for a specific organizational challenge: increase Lidl’s average spending per ticket in Portugal. Despite having a similar number of buyers as the leading retailers, Lidl customers spend less amount on each trip. A literature review suggested that Customer Loyalty is fundamental to tackle this issue, since it strengthens commitment and rewards customers for repeated and/or additional purchases. These insights were sustained by the survey questionnaire findings. There fore, a Loyalty Program is the main recommendation for solving the challenge. This Work Project aims to develop and create a Loyalty Program (LP) suited for Lidl has it aims to increase market share and average spending per ticket of Lidl in Portugal. The different types of loyalty programs are reviewed with a market background on Lidl and its competitors’ past initiatives being provided. Recommendations with required steps and elements to be taken into consideration by Lidl when designing, implementing and managing an effective loyalty program are provided, discussing the benefits, from rewards to partnerships, and the overall objectives of the LP.